Antioxidant and Antimutagenic Activities of Optimized Extruded Desi Chickpea (Cicer arietinum L) Flours - Tiznado, José Antonio Garzón; Palazuelos, Mar de Jesús Heiras; Moreno, Ramona Julieta Espinoza; Campos, Mirta Cano; Vargas, Francisco Delgado; Dorado, Roberto Gutiérrez; Carrillo, Jorge Milán; Moreno, Cuauhtémoc Reyes (Journal of Pharmacy and Nutrition Sciences, 2013)
The objective of this study was to evaluate the effect of optimized extrusion cooking process on antioxidant and antimutagenic properties of desi chickpea cultivars. Three desi chickpea cultivars (Brown-ICC3512, Red-ICC13124, Black-ICC3761) were studied. Extrusion was carried out in a single-screw extruder; the operation conditions were previously optimized to obtain maximum antioxidant activity in extruded chickpea flour: Extrusion temperature (ET) = 155°C, and screw speed (SS) = 240 rpm. The antioxidant activity (AOA) was evaluated using the oxygen radical absorbance capacity (ORAC) assay. Antimutagenic activity (AMA) of ground samples extracts was tested against 1-Nitropyrene (1-NP) with the Kado microsuspension assay using Salmonella typhimurium strain TA98. The total phenolic (TPC) and flavonoid (TFC) contents, AOA, and AMA of raw desi chickpea cultivars ranged from 1.31 to 1.35 mg GAE g-1 sample, dw, from 0.464 to 1.006 mg CAE g-1 sample, dw, from 54.9 to 57.3 mmol TE g-1 sample, dw, and from 57.8-62.3% inhibition, respectively. Brown-ICC3512 showed the highest TFC and AOA, while Red-ICC13124 had the highest AMA. The extrusion cooking process increased the TPC, AOA and AMA of whole desi chickpea grains in 5.3-9.2%, 9.9-12.2%, and 17.5-21.9%, respectively. The optimized extrusion cooking process is a recommended technology for increasing AOA and AMA in desi chickpea grains, which could be used as functional foods.